An 18F-FDG PET/CT-based radiomics nomogram for predicting progression-free survival in nasopharyngeal carcinoma: a retrospective cohort study - Lin, Jianpeng; Liu, Jinghua; Liu, Yanli; Cao, Zhendong; Wen, Dong; Wu, Yanjun; Wang, Zhongxiao; Zhang, Xiaolei; Wang, Bingzhen; Li, Shuyan; Dong, Xianling (Wolters Kluwer Health, 2026)
This study aimed to develop and validate a positron emission tomography/computed tomography (PET/CT)-based nomogram for individualized prediction of 3-year progression-free survival (PFS) in patients with nasopharyngeal carcinoma (NPC). A total of 128 patients with NPC who underwent pretreatment PET/CT imaging were retrospectively enrolled. Radiomic features were extracted from PET and CT images, and clinical variables were collected. Feature selection was performed using univariate Cox analysis, multivariable Cox analysis, and the least absolute shrinkage and selection operator regression to identify independent predictors. A nomogram was constructed by integrating CT-Radscore, PET-Radscore, and key clinical variables. Model performance in predicting 3-year PFS was evaluated using the concordance index, time-dependent area under the receiver operating characteristic curve, Kaplan-Meier survival curves, calibration curves, and decision curve analysis in both training and validation cohorts. The nomogram incorporating CT-Radscore, PET-Radscore, and lactate dehydrogenase demonstrated robust predictive ability for PFS in NPC. The area under the receiver operating characteristic curve for predicting 3-year PFS was 0.813 in the training cohort and 0.739 in the validation cohort. The corresponding concordance index values were 0.705 and 0.635, respectively. Calibration plots and decision curve analysis confirmed the nomogram's reliability and clinical utility. A PET/CT-based radiomics nomogram (CT-Radscore, PET-Radscore, and lactate dehydrogenase) achieved robust prediction of 3-year PFS and enhanced prognostic stratification in NPC. External validation in larger multi-center cohorts is needed due to the single-center retrospective design and moderate sample size.